1996
DOI: 10.1016/s0092-8674(00)80078-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PAX6 Gene Dosage on Development: Overexpression Causes Severe Eye Abnormalities

Abstract: Aniridia in man and Small eye in mice are semidominant developmental disorders caused by mutations within the paired box gene PAX6. Whereas heterozygotes suffer from iris hypoplasia, homozygous mice lack eyes and nasal cavities and exhibit brain abnormalities. To investigate the role of gene dosage in more detail, we have generated yeast artificial chromosome transgenic mice carrying the human PAX6 locus. When crossed onto the Small eye background, the transgene rescues the mutant phenotype. Strikingly, mice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
302
4
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(325 citation statements)
references
References 40 publications
14
302
4
1
Order By: Relevance
“…Pax6 is upstream of Sox2 (Furuta and Hogan, 1998), Pax6 and Sox2 cooperatively regulate gene expression (Kamachi et al 2001, Aota et al, 2003, and Sox2 is required for the maintenance of Pax6 (Donner et al, in press). Appropriate temporal, spatial, and quantitative control of Pax6 expression is required for appropriate lens morphogenesis (Hill et al, 1991;Glaser et al, 1994;Hanson et al, 1994;Grindley et al, 1995;Quinn et al, 1996;Schedl et al, 1996;Brown et al, 1998;Ashery-Padan et al, 2000;Duncan et al, 2000;van Raamsdonk and Tilgham, 2000;Dimanlig et al, 2001;Duncan et al, 2004). PAX6 mutation is causative for several congenital eye defects in humans including aniridia, Peters' anomaly and cataract (reviewed in Prosser and van Heyningen, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Pax6 is upstream of Sox2 (Furuta and Hogan, 1998), Pax6 and Sox2 cooperatively regulate gene expression (Kamachi et al 2001, Aota et al, 2003, and Sox2 is required for the maintenance of Pax6 (Donner et al, in press). Appropriate temporal, spatial, and quantitative control of Pax6 expression is required for appropriate lens morphogenesis (Hill et al, 1991;Glaser et al, 1994;Hanson et al, 1994;Grindley et al, 1995;Quinn et al, 1996;Schedl et al, 1996;Brown et al, 1998;Ashery-Padan et al, 2000;Duncan et al, 2000;van Raamsdonk and Tilgham, 2000;Dimanlig et al, 2001;Duncan et al, 2004). PAX6 mutation is causative for several congenital eye defects in humans including aniridia, Peters' anomaly and cataract (reviewed in Prosser and van Heyningen, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…This dose-response analysis revealed that the increase of ␣ cells and of glucagon transcripts was maximal with 1.5 ng of injected Mo2 corresponding to a mild reduction of pax6b activity. Previous studies have shown that a precise range of the Pax6 protein level is important for the proper development of the eyes, brain, and pancreas because an increase of Pax6 expression in transgenic mice leads to abnormalities in these organs (19,20,34). Moreover, heterozygous Pax6 individuals display anomalies in eye morphology and brain patterning (10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, overexpression of Pa 6 was shown to disturb the normal development of beta cells. In the development of eyes, overexpression of Pa 6 in transgenic mice was also reported to cause severe microphthalmia although appropriate expression of Pa 6 rescued eye abnormalities observed in Small eye mice which have mutations in the Pa 6 gene [22].…”
Section: Discussionmentioning
confidence: 99%